2021
DOI: 10.3390/math9141591
|View full text |Cite
|
Sign up to set email alerts
|

Can Mathematics Achievement Be Predicted? The Role of Cognitive–Behavioral–Emotional Variables

Abstract: The current society is based on science and technology, depending partly on mathematics. It leads to citizens’ success in school mathematics, being measured through achievement, which can be predicted by affective, cognitive, and behavioral variables. The aim of this study was to determine the extent to which self-concept, learning strategies, attitude towards science and mathematics, school environment, and previous scores in science and mathematics predict achievement in mathematics. A convenience sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Additionally, other studies reported that students' cognitive (e.g., paraphrasing and deductive inferencing) or metacognitive abilities (e.g., monitoring) were positively related to their science achievement in chemistry (Gonzá lez & Paoloni, 2015;Rahman et al, 2010) and biology (Cromley et al, 2021). On the other hand, some studies failed to show an association between metacognitive skills and mathematical achievement (Ferná ndez-Cé zar et al, 2021;Rosenzweig et al, 2011).…”
Section: Relations Between Mental Processes and Stem Performancementioning
confidence: 99%
“…Additionally, other studies reported that students' cognitive (e.g., paraphrasing and deductive inferencing) or metacognitive abilities (e.g., monitoring) were positively related to their science achievement in chemistry (Gonzá lez & Paoloni, 2015;Rahman et al, 2010) and biology (Cromley et al, 2021). On the other hand, some studies failed to show an association between metacognitive skills and mathematical achievement (Ferná ndez-Cé zar et al, 2021;Rosenzweig et al, 2011).…”
Section: Relations Between Mental Processes and Stem Performancementioning
confidence: 99%